2024
DOI: 10.1186/s12888-024-05765-5
|View full text |Cite
|
Sign up to set email alerts
|

Asparagine reduces the risk of schizophrenia: a bidirectional two-sample mendelian randomization study of aspartate, asparagine and schizophrenia

Huang-Hui Liu,
Yao Gao,
Dan Xu
et al.

Abstract: Background Despite ongoing research, the underlying causes of schizophrenia remain unclear. Aspartate and asparagine, essential amino acids, have been linked to schizophrenia in recent studies, but their causal relationship is still unclear. This study used a bidirectional two-sample Mendelian randomization (MR) method to explore the causal relationship between aspartate and asparagine with schizophrenia. Methods This study employed summary data fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
0
0
Order By: Relevance
“…Mendelian randomization of selected instrumental variables for genetic variation must be based on three fundamental assumptions: the correlation hypothesis, which postulates a strong correlation between SNPs and exposure factors; the independence hypothesis, which asserts that SNPs are not affected by various confounders; and the exclusivity hypothesis, which argues that SNPs affect the outcome only through exposure factors 25 , 26 . In our study, IVs for each immune phenotype were identified with a stringent significance threshold of 5e-8, employing PLINK (v1.90) for SNP trimming based on linkage disequilibrium (LD; r2 < 0.001 within a 10,000 kb radius).…”
Section: Methodsmentioning
confidence: 99%
“…Mendelian randomization of selected instrumental variables for genetic variation must be based on three fundamental assumptions: the correlation hypothesis, which postulates a strong correlation between SNPs and exposure factors; the independence hypothesis, which asserts that SNPs are not affected by various confounders; and the exclusivity hypothesis, which argues that SNPs affect the outcome only through exposure factors 25 , 26 . In our study, IVs for each immune phenotype were identified with a stringent significance threshold of 5e-8, employing PLINK (v1.90) for SNP trimming based on linkage disequilibrium (LD; r2 < 0.001 within a 10,000 kb radius).…”
Section: Methodsmentioning
confidence: 99%